2010
DOI: 10.1007/s11892-010-0133-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gene Associations in Type 1 Diabetes

Abstract: Recent genome-wide association studies have been able to identify multiple new gene loci affecting type 1 diabetes susceptibility, but the impact of these new defined loci seems to decrease in parallel with their number. The HLA gene region remains the main nominator of genetic susceptibility, although the identity of important genes and especially the mechanisms of their action are still largely unclear. Products of HLA and most other known risk genes are involved in regulation of the immune system in accorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…To estimate the strength of the HLA class II association in the prediction of disease risk, we classified genotypes according to the presence of susceptible, protective, and neutral haplotypes into six groups as described earlier and compared the findings with that observed in the Finnish population . The Egyptian patients were strongly concentrated to groups with combinations of risk‐associated haplotypes: 71 of 101 (70.3%) Egyptian children with T1D had this type of genotype compared with only 217 of 622 Finnish children (34.9%, p = 1.6E−11).…”
Section: Resultsmentioning
confidence: 99%
“…To estimate the strength of the HLA class II association in the prediction of disease risk, we classified genotypes according to the presence of susceptible, protective, and neutral haplotypes into six groups as described earlier and compared the findings with that observed in the Finnish population . The Egyptian patients were strongly concentrated to groups with combinations of risk‐associated haplotypes: 71 of 101 (70.3%) Egyptian children with T1D had this type of genotype compared with only 217 of 622 Finnish children (34.9%, p = 1.6E−11).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the proportion of high-risk HLA genotypes has decreased among patients diagnosed with T1D during recent decades compared with those diagnosed a few decades earlier (Gillespie et al, 2004;Hermann et al, 2003). This change is associated with a greatly increased disease incidence during the past decades and indicates that greater environmental pressure affects the penetrance of T1D in genotypes with lower HLA risk (Ilonen and Hermann, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Twin studies have confirmed the importance of heritage with a concordance rate of up to 70% (6). At least 10 genes have been reported to be involved, the most dominant being the HLA‐class II presenting gene on the short arm of chromosome 6, where some haplotypes (DR/DQ) are considered high risk alleles (7,8).…”
Section: Introductionmentioning
confidence: 99%